Pengaruh Iklim Organisasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Studio Prewedkita Di Kabupaten Tangerang - Hadi, Rusman; Hindriari, Reni (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstrak. This study aims to determine the Influence of Organizational Climate and Work Discipline on Employee Performance in our prewed studio. both partially and simultaneously. This type of research uses a quantitative method with a saturated sample of 50 respondents. The results of the analysis of work experience partially affect employee performance with a simple linear regression equation Y = 17.209 + 0.572 X1. The correlation coefficient of 0.576 means it has a moderate level of relationship and a coefficient of determination of 33.2% means that performance is influenced by organizational climate by 66.8%. This is proven by the t test obtained t count value> t table (3.369> 2.010) and strengthened by a significant value <0.05 (0.000 <0.05). Work discipline partially has a positive effect on employee performance, a simple linear regression equation Y = 23.129 + 0.432 X2. The correlation coefficient of 0.447 means it has a moderate relationship and a coefficient of determination of 20.0% means that performance is influenced by work discipline by 8%. This is proven by the t test obtained the calculated t value > t table (1.322 < 2.010) and is strengthened by a significance value < 0.05 (0.000 < 0.05). The results of the study of organizational climate and work discipline simultaneously on employee performance, the multiple linear regression equation Y = 14.218 + 0.470 X1 + 0.179 X2, the correlation coefficient of 0.596 means it has a moderate level of relationship and a determination coefficient of 35.6% means that performance is influenced by organizational climate and work discipline by 64.4%. the results of the F test hypothesis test obtained the calculated F value > F table (12.968 > 3.19) and is strengthened by a significance value < 0.05 (0.000 < 0.05). Thus it is proven that Ho is rejected and Ha is accepted Keywords: Organizational Climate, Work Discipline, Employee Performance